2020
DOI: 10.1002/aelm.202000080
|View full text |Cite
|
Sign up to set email alerts
|

Achieving High Alignment of Conjugated Polymers by Controlled Dip‐Coating

Abstract: Realizing high polymer chain orientation and ordered thin‐film microstructures is beneficial for efficient charge transport of conjugated polymers. However, achieving a high alignment degree remains a challenge due to the sensitive nature of polymers to the processing conditions. By simply varying concentrations during a dip‐coating method, the component of polymer aggregates that adopt the planar backbones is enlarged and the ensuing assembly process is promoted. Herein, highly oriented polymer thin films of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 56 publications
(75 reference statements)
0
33
0
Order By: Relevance
“…Taking OPV as an example, the presence of π–π stacking at the molecular level and the locally ordered phase is of great importance to exciton diffusion, dissociation and charge transport within the photoactive layer [18–20] . For OFETs, efficient charge injection and transport rely on the ordered structure at both molecular and device‐size scales [21–23] . A typical characteristic of solution‐processed organic semiconductors is that the aggregation and ordering process can occur at various conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Taking OPV as an example, the presence of π–π stacking at the molecular level and the locally ordered phase is of great importance to exciton diffusion, dissociation and charge transport within the photoactive layer [18–20] . For OFETs, efficient charge injection and transport rely on the ordered structure at both molecular and device‐size scales [21–23] . A typical characteristic of solution‐processed organic semiconductors is that the aggregation and ordering process can occur at various conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In 2020, Pei et al reported the fabrication of P308-based OFET's fabricated using the dip-coating method. 131 The fast coating speed and the short relaxation time of the transition region facilitated the planarization of the polymer backbone. A high mobility of 8.31 cm 2 V À1 s À1 was recorded when the coating speed was 15 μm s À1 .…”
Section: Iid-derived Polymers For Fabrication Of Ofet'smentioning
confidence: 99%
“…According to the available data, the most studied polymeric isoindigos are dithienyl derivatives, in which two thiophene fragments can be linked to each other [74][75][76][77][78][79][80][81][82][83][84][85][86] or be separated by spacers of different structures [87][88][89][90][91]. Structures containing a 2,2'-dithienyl fragment can be divided into three types: 1) not containing substituents in the benzo and thienyl fragments; 2) containing fluorine atoms in the thienyl fragment; and 3) containing fluorine atoms in positions 7,7' and in thienyl fragments (Scheme 24).…”
Section: Isoindigo As the Basis For Organic Field-effect Transistors (Ofet)mentioning
confidence: 99%
“…In contrast to the traditional spin-coating technique, the authors succeeded in obtaining a thin film by immersing a substrate in a polymer solution, followed by slow extraction, accompanied by slow evaporation of the solvent. The device thus obtained showed one of the highest values of hole conductivity of μ e = 8.3 cm 2 ⋅V −1 ⋅s −1 [ 78 ]. It was also found that a device based on compound 45 (R = 2-decyltetradecyl) with the addition of iron phthalocyanine showed slightly better mobility.…”
Section: Reviewmentioning
confidence: 99%